TYPES AND TRUST SYSTEMS BASED ON THE IDEOLOGY OF BUGIS COMMUNITY CULTURE ON LOCAL INTEREST VALUES IN CENNING RARA SPELLS - Muhsyanur Muhsyanur (Sanata Dharma University, 2020)
This research analyzes the type and belief system based on the Bugis cultural ideology of the values of local wisdom in the cenning rara spells. This research is a descriptive qualitative research by having two sources of data, which are spells and responses or opinions of Bugis people about spells. This type of research data in the form of words, phrases, expressions, and statements, both from the contents of the spell and from the opinion of the Bugis community about spells. The approach used in research, namely the ethnographic approach. The work method of ethnographic approach is that the researcher is directly involved in the field or the Bugis community environment to obtain more accurate data. The data analysis technique used for the data collected is a cultural interpretation technique. The results showed that there are three types and cultural ideology contexts of the Bugis community in the cenning rara spells, namely (1) the enchanting cenning rara spells that is considered effective in capturing the hearts of the opposite sex, (2) the power cenning rara spells which is considered as a thickener, and (3 ) cenning rara spells treatment that is considered a young preservative.